Explaining Disclosed Marital Infidelity in Men Based on the Inter-Systemic Model - Baratian, Amin; Kimiaei, Seyed Ali; Kareshki, Hossein; Ahmadi, Khodabakhsh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explain the phenomenon of disclosed marital infidelity in men through the lens of the inter-systemic model.Methods and Materials: This qualitative study employed a multiple-stage design using semi-structured interviews. The participants were 15 men aged 30–45 who had engaged in marital infidelity, which had been disclosed either voluntarily or by their spouses, and who sought counseling services in Tehran. Participants were recruited through criterion-based purposive sampling, ensuring inclusion criteria such as having at least a high school diploma, no intellectual disabilities, no current psychological treatment, and no marital separation. Data were collected through in-depth, face-to-face interviews guided by a question framework developed and validated by family studies experts. Interviews were transcribed verbatim and analyzed using qualitative content analysis to identify themes, categories, and systemic linkages. Ethical principles of voluntary participation and confidentiality were strictly observed throughout the study.Findings: Analysis revealed that men’s infidelity stemmed from complex interconnections among multiple systems. Individual factors included sexual dissatisfaction, egocentrism, sensation-seeking, and emotional distress. Relational factors encompassed emotional withdrawal, conflict avoidance, sexual monotony, and ambivalent attachment. Familial influences included dysfunctional parenting patterns, blurred boundaries, and in-law interference. Socio-cultural factors involved gendered double standards, economic stressors, and technological affordances that facilitated external relationships. These systems interacted dynamically, showing infidelity as a maladaptive coping strategy used to escape emotional stagnation rather than solely as a pursuit of sexual gratification.Conclusion: Disclosed marital infidelity in men emerges from the cumulative interaction of individual, relational, familial, and socio-cultural systems. The inter-systemic model offers a comprehensive framework for understanding this phenomenon and can inform targeted, multi-level interventions for prevention and treatment.